2007
DOI: 10.1021/la062405o
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Urea and Its Homologue Glycinamide:  Conformations, Rotational Barriers, and Relative Interactions with Sodium Chloride

Abstract: Conformational behaviors of urea and glycinamide have been investigated using the B3LYP functional with the 6-311+G* and 6-311+G** basis sets. Urea monomers have nonplanar minima at all the levels studied, even in the aqueous phase. In the case of glycinamide, the intramolecular hydrogen bond formed from the amide to the amine is important for stabilizing the global minimum. Bond rotations and nitrogen inversion barriers for glycinamide conformations have also been reported. The DFT calculated results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…1). We have observed that the relaxation of slab layers does not affect the interaction of organic additives with surfaces [56][57][58], however, it is important to examine the effect of relaxations of slabs with inorganic ions like Cd 2+ . Relaxing the top layer of {1 0 0} and {1 1 1} surface of NaCl with Cd 2+ predicted the similar trend as observed with the fixed surfaces (Supporting information, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). We have observed that the relaxation of slab layers does not affect the interaction of organic additives with surfaces [56][57][58], however, it is important to examine the effect of relaxations of slabs with inorganic ions like Cd 2+ . Relaxing the top layer of {1 0 0} and {1 1 1} surface of NaCl with Cd 2+ predicted the similar trend as observed with the fixed surfaces (Supporting information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, DFT calculated results also revealed that the kink site is more energetically favored than that of flat and step surfaces towards the growth of specific planes compared to steps or ledge sites [2,12]. The magnitude of interaction calculated in the case of Cd 2+ ion is much higher than the organic additives on such surfaces [57][58][59][60]. The calculations performed in water employing the continuum model (COSMO) however, showed reasonably Table 1 Interaction energies calculated at GGA/VWN-BP/DNP for gas phase and GGA/VWN-BP/DNP for aqueous phase (COSMO) level using LDA/PWC/DND optimized geometries for Cd 2+ ion with {1 0 0} and {1 1 1} flat, step and kink sites of NaCl surfaces in kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38][39] Three-dimensional (3D) slabs of sodium chloride [{100} and {111}] were generated employing periodic boundary conditions. 6,7 The optimization of additive on the surface was performed with LDA/PWC/DND level of theory and the interaction energies were reported with GGA/PW91/DND level. The conductor-like screening model (COSMO) was employed to take into account the solvent (water) in our calculations.…”
Section: Computational Methodologymentioning
confidence: 99%
“…The compositions at this pH value are a 0 ¼ 0.02659, a 1 ¼ 0.62638, a 2 ¼ 0.34263, a 3 ¼ 4.4 Â 10 À4 . [6][7][8][9] 3.4 Molecular electrostatic potential (MESP) analysis of citric acid and its dissociated forms…”
Section: Determination Of the Composition Of Polyprotic Acid As A Fun...mentioning
confidence: 99%
See 1 more Smart Citation